2012
DOI: 10.1007/s00380-012-0253-6
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial thickness under the catheter ablation lines in patients with paroxysmal atrial fibrillation: insights from 64-slice multidetector computed tomography

Abstract: A detailed understanding of the left atrial (LA) anatomy in patients with atrial fibrillation (AF) would improve the safety and efficacy of the radiofrequency catheter ablation. The objective of this study was to examine the myocardial thickness under the lines of the circumferential pulmonary vein isolation (CPVI) using 64-slice multidetector computed tomography (MDCT). Fifty-four consecutive symptomatic drug-refractory paroxysmal AF patients (45 men, age 61 ± 12 years) who underwent a primary CPVI guided by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 27 publications
2
51
1
Order By: Relevance
“…Yokokawa et al found an increase in LA roof thickness of 1–2 mm [24]. While our baseline measured wall thickness of 7 mm is greater than that reported by CT imaging (1–4 mm) [38], [39]. This is likely due to 5 mm slice thickness which could cause partial-voluming of the LA wall with other tissues, or increased apparent thickness due to the LA wall curvature.…”
Section: Discussioncontrasting
confidence: 67%
“…Yokokawa et al found an increase in LA roof thickness of 1–2 mm [24]. While our baseline measured wall thickness of 7 mm is greater than that reported by CT imaging (1–4 mm) [38], [39]. This is likely due to 5 mm slice thickness which could cause partial-voluming of the LA wall with other tissues, or increased apparent thickness due to the LA wall curvature.…”
Section: Discussioncontrasting
confidence: 67%
“…Atrial stretch shortens the effective refractory period, increases the dispersion of the atrial effective refractory period, and potentiates the activity of ectopic triggers [21][22][23]. (2) The thickness of the left atrium exhibits a great variation between regions within the left atrium and among different patients [24]. Atrial tissue in hearts with LVH may differ from atrial tissue in hearts without LVH.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…4). A number of CT studies have identified differences in the thickness of the atrial wall between patients with conditions that elevate the atrial pressure [65][66][67]. A dependence of the atrial wall thickness on the presence of atrial fibrillation has also been demonstrated, and among patients undergoing catheter ablation procedures, local atrial electrophysiological phenomena have been localized to regions of greater wall thickness [68][69][70].…”
Section: Atrial Wall Thickness Measurementmentioning
confidence: 97%